2004
DOI: 10.1523/jneurosci.0481-04.2004
|View full text |Cite
|
Sign up to set email alerts
|

Encoding-Specific Effects of Social Cognition on the Neural Correlates of Subsequent Memory

Abstract: To examine whether social cognition recruits distinct mental operations, we measured brain activity during social ("form an impression of this person") and relatively nonsocial ("remember the order in which person information is presented") orienting tasks. Extending previous research on the neural basis of social cognition, the impression formation task differentially engaged an extensive region of the dorsomedial prefrontal cortex (PFC). In contrast, the nonsocial sequencing task differentially engaged the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
188
2
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 225 publications
(214 citation statements)
references
References 50 publications
23
188
2
1
Order By: Relevance
“…As illustrated in Figure 5, the region of medial prefrontal cortex (BA 32) is superior to the self-reference activity displayed in Figure 3, but is consistent with previous reports of the involvement of dorsal medial prefrontal cortex in self-referential processes (Mitchell, Macrae, & Banaji, 2004;Mitchell et al, 2005). As displayed in Figure 5, the age groups differ in their response to items judged in reference to the self, with elderly activating strongly to positive but not negative items, while young activate somewhat more for negative than positive items.…”
Section: Neuroimaging Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…As illustrated in Figure 5, the region of medial prefrontal cortex (BA 32) is superior to the self-reference activity displayed in Figure 3, but is consistent with previous reports of the involvement of dorsal medial prefrontal cortex in self-referential processes (Mitchell, Macrae, & Banaji, 2004;Mitchell et al, 2005). As displayed in Figure 5, the age groups differ in their response to items judged in reference to the self, with elderly activating strongly to positive but not negative items, while young activate somewhat more for negative than positive items.…”
Section: Neuroimaging Resultssupporting
confidence: 90%
“…Although we suggest that emotion generally is incidental to the task, previous studies identify dorsal medial prefrontal activation during impression formation (Mitchell et al, 2004;Mitchell et al, 2005). Taken together with our finding, the activity of the region may reflect evaluative components that are more salient for older adults, but only during selfreferencing.…”
Section: Discussionsupporting
confidence: 64%
“…The TPJ, frequently bilaterally, is consistently involved in tasks requiring the attribution of mental states to social targets (Saxe & Wexler, 2005;Saxe, 2006;Spreng, Mar, & Kim, 2008) and damage to this brain area has been shown to impair performance on Theory of Mind (ToM) tasks (Samson, Apperly, & Humphreys, 2004). The MPFC is also central to many social cognitive processes (Amodio & Frith, 2006), including those supporting impression formation (Mitchell, Macrae, & Banaji, 2004), ToM and the perception of faces for which person-knowledge is available (Cloutier, Kelley, & Heatherton, 2011;Todorov, Gobbini, Evans, & Haxby, 2007). Accordingly, preferential involvement of the TPJ and MPFC for incongruent social targets provides additional evidence in support of person perception models positing the frequent necessity to individuate targets violating social expectations (Brewer, 1988;Fiske & Neuberg, 1990;Macrae et al, 1999).…”
Section: Individuation and Mental State Inferencesmentioning
confidence: 99%
“…Neuroimaging and lesion studies have shown that social tasks activate specific brain areas that can be distinguished from those activated by non-social tasks, for example superior temporal sulcus, medial prefrontal cortex (Adolphs, 2001;Harris et al, 2005;Mitchell et al, 2004), amygdala, fusiform gyrus and insular regions (Bar-On R et al, 2003). Consecutively, the MATRICS-NIMH consensus cognitive battery for schizophrenia categorized social cognition as one of the seven major separate cognitive domains that are altered in schizophrenia, alongside with: Speed of Processing, Attention/vigilance, Working Memory, Verbal Learning and Memory, Visual learning and Memory and Reasoning and Problem Solving (Green et al, 2004).…”
Section: Introductionmentioning
confidence: 99%